Proposing a Breast Abscess Pathway to Guide General Surgeons: A Retrospective Audit - Naseem, Salma; Hamad, Ahmed (Medical Science: Trends and Innovations Vol. 12, 2025)
Breast infections constitute one of the most common emergencies presenting to the accident and emergency globally, with the condition ranging from mild infection to sepsis. Breast infection/abscess is a fairly common surgical emergency presenting in the A&E department in the UK. These patients are managed by the accident and emergency staff and the on-call general surgeons. Management is variable depending on the expertise of the staff attending to this group. This may lead to unnecessary hospital admission, perhaps culminating in patient dissatisfaction and injudicious use of resources. Herein, based on a single-center study, a simple, clear, and pragmatic pathway is proposed for acute breast infections. This is a retrospective audit of patients in the 10-month period from January to October 2016 admitted with breast infections. Symptoms for attendance, duration of stay, time taken for an ultrasound examination, clinical course, and follow-up were examined. Radiological assessment was recorded by picture archiving and communication system (PACS). Among all the subjects, 24 patients presented with symptoms suggesting infection/abscess, one presented with mastalgia without any obvious history of trauma, one had metastatic breast cancer and presented with hypercalcemia, and five cases had non-infected postoperative complications. Out of the total number of admissions to the SAU (31 patients), 67% or 21 patients required ultrasound evaluation. All patients received antibiotics regardless of the initial management. The proposed pathway addresses complete evaluation and states both the indications for conservative and open surgical management. It is hoped that this would achieve an improved patient experience, leading to service improvement by eliminating variability of care.